2023
DOI: 10.14245/ns.2346610.305
|View full text |Cite
|
Sign up to set email alerts
|

Spine Surgical Robotics: Current Status and Recent Clinical Applications

Jiangtao Wang,
Junxian Miao,
Yi Zhan
et al.

Abstract: With the development of artificial intelligence and the further deepening of medical-engineering integration, spine surgical robot-assisted (RA) technique has made significant progress and its applicability in clinical practice is constantly expanding in recent years. In this review, we have systematically summarized the majority of literature related to spine surgical robots in the past decade, and not only classified robots accordingly, but also summarized the latest research progress in RA technique for scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…Kantelhardt et al ( 27) first reported an accurate placement rate of 94.5% for robot-guided pedicle screw placement compared with a 91.4% accuracy rate for traditional screw placement. Several subsequent studies have also demonstrated that robot-assisted screw placement is superior in accuracy to traditional methods and results in less tissue damage during surgery, thus providing a better prognosis for patients (28)(29)(30)(31)(32). Moreover, undoubtedly, the future of spinal robotics should not be limited to assisting surgeons in pedicle screw placement alone.…”
Section: Discussionmentioning
confidence: 99%
“…Kantelhardt et al ( 27) first reported an accurate placement rate of 94.5% for robot-guided pedicle screw placement compared with a 91.4% accuracy rate for traditional screw placement. Several subsequent studies have also demonstrated that robot-assisted screw placement is superior in accuracy to traditional methods and results in less tissue damage during surgery, thus providing a better prognosis for patients (28)(29)(30)(31)(32). Moreover, undoubtedly, the future of spinal robotics should not be limited to assisting surgeons in pedicle screw placement alone.…”
Section: Discussionmentioning
confidence: 99%